Flap choice does not affect complication rates or functional outcomes following extremity soft tissue sarcoma reconstruction. Issue 7 (July 2018) - Slump, Jelena; Hofer, Stefan O.P.; Ferguson, Peter C.; Wunder, Jay S.; Griffin, Anthony M.; Hoekstra, Harald J.; Bastiaannet, Esther; O'Neill, Anne C.
Summary: Background: Flap reconstruction plays an essential role in facilitating limb preservation in patients with extremity soft tissue sarcoma (ESTS). However, the effect of flap choice on the rates of postoperative complications and functional outcomes has not been clearly established. This study directly compares the outcomes of free and pedicled flap reconstructions in patients with ESTS. Methods: Two hundred sixty-six patients who underwent flap reconstruction following ESTS resection were included. Associations between flap type and complications were determined using logistic regression analyses. Functional outcome was evaluated using the Toronto Extremity Salvage Score (TESS) and the Musculoskeletal Tumor Society Scales (MSTS). Results: There was no significant difference between complication rates in the pedicled and free flap groups (32% vs. 38%, p = 0.38). In the lower limb, pedicled flaps had complication rates similar to those of free flaps on univariate analysis (odds ratio [OR] = 1.12, 95% confidence interval [CI] = 0.56–2.26, p = 0.75). Conversely, in the upper limb, pedicled flaps were associated with fewer complications on univariate analysis (OR = 0.31, 95% CI = 0.11–0.86, p = 0.03), but this was not significant on multivariate analysis (OR = 0.45, 95% CI = 0.13–1.59, p = 0.22). Obesity was a strong predictor of complications in the upper limb group on multivariate analysis (body mass index [BMI] ≥ 30 kg/m 2, OR = 7.01, 95% CI = 1.28–38.51, p = 0.03). There was no significant difference in functional outcomes between both flap groups in either upper or lower limbs. Conclusions: Postoperative complications and functional outcomes for patients undergoing free and pedicled flaps are similar in ESTS reconstruction. Selecting the most suitable reconstructive option in each individual case is paramount to preserving function while minimizing postoperative morbidity.